Family support indices for substance abuser in Terengganu - A., Fazillah; H., Juahir; E., Toriman; N., Mohamad; M. K. A., Kamarudin; A., Fairuz; S. M. H. S, Omar; G, Adiana; M., Mohamad (International Journal of Engineering and Technology, 2018)
Substance abuse has been a longstanding global issue. Efforts are continuing to find solutions. Family support is important and occurs in different forms. This study was designed to identify factors influencing family support and to relate them to the types of support given to help develop family support indices. Factors deemed to influence family support were identified and subjected to factor analysis to deter-mine the association. A family support index was developed based on the four types of family support investigated. The scale categories ranging from very good to very poor as the indicator for the level of family support in the study area. Family support indices for the four types of support were high. The form of family support with the highest index score was â€˜instrumental supportâ€™. We concluded that sub-stance abusers received good family support with the highest score recorded for instrumental support. The indices developed can help au-thorities obtain a comprehensive picture of support given and design programs to use optimally family support in the management of sub-stance abuse.Â